Histological Studies in Animal Model of Helicobacter pylori Infection Treated with Attacin A Antimicrobial Peptide - Mohamed, Doaa M.; Khaled, Howayda E.; Youssef, Tito N.; Wassim, Nahla M. (Journal of Advanced Veterinary Research, 2023)
Recent years have seen an upsurge in the demand for alternative treatment agents due to the advent of antibiotic-resistant strains of Helicobacter pylori (H. pylori). Small peptides belonging to the class known as antimicrobial peptides (AMP) are an essential component of the innate immune systems of many different types of organisms. The goal of this study to detect histological changes in rat animal models infected with H. pylori and treated with the antimicrobial peptide Attacin A (AttA) and its effectiveness as anti-H. pylori. The purpose of this research was to determine the efficacy of the AttA against H. pylori by observing any histological alterations that occurred in an H. pylori-infected rat model after treatment with AttA. Three groups of rats (normal control and H. pylori-infected and H. pylori-infected and treated with AttA). Stomachs were examined histologically to evaluate the AttA therapeutic activity. In conclusion, the results of the current study showed the effect of the AttA on reducing the severity of the infection of H. pylori and reducing the tissue damage in the lining of the stomach of rats.